Evaluación del riesgo de inundación utilizando análisis hidrográfico en San Juan de Las Cucarachas, Manabí - Márquez Mera, Pamela Selena (2023)
The objective of this degree work is to evaluate the flood risk of the San Juan de las Cucarachas community, which was evaluated through the variables threat and vulnerability for territorial planning. Through its exploratory scope, it intends to condition the land in academic terms for the development of future studies for the benefit of the community. Flood risk management is possible thanks to procedures through the analysis of meteorological data and hydrographic characterization of the area of interest. Through the interpretation of hydrological and meteorological data, using observation as a technique, the population used for data collection was the meteorological stations that have an impact on the Guayas basin, and also using a convenience sampling, choosing the stations closest to the basin through triangulation. It was determined that precipitation, time of concentration, duration, type of basin, river sinuosity and the location of the San Juan basin in reference to the Guayas basin were identified as threats. In addition, among the vulnerabilities, the morphological characteristics of the basin, topography and the altimetry of the riverbed were identified.